Substance Use Depictions in Malayalam Cinema: A Systematic Movie Content Analysis - Sivaranjini, M.; Bharadwaj, Yatheesh; Jayalakshmi, KJ; Tharakan, Akhil; Haritha, K (Sahayaatra सहयात्रा, 2026)
Malayalam movie occupies a distinctive position among India’s regional film industries, long celebrated for its commitment to social realism. This study presents the first systematic content analysis of substance use depictions in Mollywood industry of Kerala State in India. We have drawn a sample of 30 commercially successful Malayalam movies released between 1991 and 2000. Three top-grossing films were selected for each year and every substance-related scene was crucially observed and coded using a structured observation tool. The scenes were categorized by type of substance, mode of depiction, their settings, and the character type and number of persons involved in each scene. We identified a total of 103 substance-related scenes, and an average of 4.37 scenes per movie. The results shows that among the substances portrayed, alcohol was depicted most frequently (37.8%), followed by tobacco (30.1%), illicit drug portrayals were rare (7.77%). The mode of depiction suggests that visual-only depiction accounted 44.66% of scenes, and domestic settings had a major proportion (41.75%). Hero and heroine characters were present in nearly half of all scenes (45.63%). The study underscores the need of health protective messages in the popular cinemas.